Pengaruh Marketing Mix terhadap Keputusan Pembelian Sepatu Johnson di Surabaya Selatan - Fatmadewi, Nadilia Via; Maduwinarti, Ayun; Mulyati, Awin (Research Journal of Social Science and Economics, 2025)
In Lifestyle now provides far affordability of various mixes for many markets in e-commerce transactions. As a result of the marketing mix it can be useful for developing strategies in increasing competition, of course the products can influence the marketing system well, improve product quality, better prices and of course will influence consumer purchasing decisions. To find out the positive effect between Product, Price, Location, Promotion, People, Physical Evidence, and Process on Buying Decisions for Johnson Shoes in South Surabaya. In this study, researchers used quantitative research methods, meaning research methods based on positivistic (concrete data), research data in the form of numbers to be measured using statistics as a means of calculating the test, related to the problem under study to produce a conclusion. Product, Price, Place , Promotion, People, Physical Evidence and Process simultaneously (together) have a significant effect on purchasing decisions at Johnson Shoe Stores. So it can be interpreted that Products, Prices, Places, Promotions, People, Physical Evidence and Processes at Johnson Shoe Stores are improved so that they can increase consumer purchasing decisions. From the results of the t (partial) test the results of the seven binding variables that are most dominantly influencing with the highest value are Promotions. Regarding the promotion variable, it is better to promote these shoes for marketing by creating promotional concepts such as cooperating with well-known artists who are on the rise and popular with many people so that it can attract many people and Johnson's shoe store can also use social media tiktok because currently tiktok is very popular with many people so that it can take a specific market share.